A new world - Smith, Jane Margaret; Kan, Pat (Newport, NSW : Big Sky Publishing Pty Ltd, 2022)
"It's not easy coming to the city all alone when you're a young country girl. It's even harder when a strange discovery sends you back in time to 1841! Carly Mills is about to learn how dangerous Sydney can be for a lonely colonial girl ... and how hard it is to move in a corset! Caroline Chisholm tells her that kindness and friendship can make the world a better place. Could Mrs Chisolm be right?" -- Back cover screen.
"A time-travelling adventure with Caroline Chisholm"-Cover screen.
Illustrations: Pat Kan.
Title from title screen.
Mode of access : Available online.
Keywords: Chisholm, Caroline, -- 1808-1877 -- Juvenile fiction; Electronic books; Time-travel fiction